Central venous catheter-related bloodstream infection caused by Staphylococcus aureus: microbiology and risk factors - Sadoyma,Geraldo (2006)
Although central vascular catheters (CVC) are indispensable in modern medicine, they are an important risk factor for primary bacteremias. We examined the incidence and risk factors associated with catheter-related bloodstream infection (CR-BSI) caused by Staphylococcus aureus in surgical patients. A prospective study was carried out in the Hospital das Clínicas da Universidade Federal de Uberlândia (HC-UFU) from September 2000 to December 2002. The skin insertion site, catheter tip, and blood were microbiologically analyzed. Demographics and risk factors were recorded for each patient, and cultures were identified phenotypically. Staphylococcus aureus was the most frequent pathogen, with an incidence rate of 4.9 episodes of CR-BSIs per 1,000 catheter/days. Based on logistic regression, the independent risk factors were: colonization on the insertion site =200 colony forming units (CFU)/20 cm² (p=0.03; odds ratio (OR) =6.89) and catheter tip (p=0.01; OR=7.95). The CR-BSI rate was high; it was mainly associated with S. aureus, and skin colonization at the insertion site and on the catheter tip were important risk factors for CR-BSI.